The Implementation Effect of the Evidence-Based Practice Plan for Rehabilitation Nursing of Stroke Swallowing Disorder - Na, Sa Ri; oyungoo, B.; Bai, Yiping (International Journal of Public Health and Medical Research, 2025)
Objective: To explore the implementation effect of the evidence-based practice plan for rehabilitation and nursing of cerebral stroke and swallowing disorders. Methods: 90 patients with cerebral stroke and dysphagia admitted to a hospital were selected and randomly divided into the experimental group and the control group, with 45 cases in each group. The experimental group implemented personalized nursing based on the evidence-based practice plan, including standardized diet management, swallowing function training and oral care; the control group adopted the traditional nursing model. Evaluate the nursing effect through the drinking water test, SWAL-QOL score and nursing satisfaction, and analyze the changes in the nursing quality of the two groups and the quality of life of patients. Results: The efficiency of nursing quality and swallowing function improvement of the experimental group (97.78%) was significantly higher than that of the control group (80.00%), the quality of life score and nursing satisfaction score are also significantly better than the control group (P<0.05). Conclusion: The evidence-based nursing plan for cerebral stroke swallowing disorder can significantly improve the nursing effect and effectively improve the patient’s swallowing function and quality of life, which is worth promoting in clinical practice.